1999
DOI: 10.1021/es9809760
|View full text |Cite
|
Sign up to set email alerts
|

Complete Reduction of TNT and Other (Poly)nitroaromatic Compounds under Iron-Reducing Subsurface Conditions

Abstract: Contamination of soils and aquifers with (poly)nitroaromatic compounds ((P)NACs) is a widespread problem. This work demonstrates that (P)NACs such as the explosive 2,4,6-trinitrotoluene (TNT) can be completely reduced to the corresponding aromatic polyamines by Fe(II) present at the surface of Fe(III)(hydr)oxides or, less efficiently, by hydroquinone moieties of (natural) organic matter in the presence of H2S. The reduction kinetics of (P)NACs were investigated in sterile batch systems as well as in columns co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
326
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(351 citation statements)
references
References 44 publications
22
326
2
1
Order By: Relevance
“…The role of the 2:1 smectite clays may be significantly different for NDMA degradation, since there is no direct link between NDMA degradation and adsorbed ferrous iron (which there is for TCE). In a similar study, reduction of nitroaromatics was caused both by adsorbed iron on edge surfaces of clays as well as structural iron in the 2:1 smectite clays (Hofstetter et al 1999(Hofstetter et al , 2003.…”
Section: Description Of Tasksmentioning
confidence: 84%
See 1 more Smart Citation
“…The role of the 2:1 smectite clays may be significantly different for NDMA degradation, since there is no direct link between NDMA degradation and adsorbed ferrous iron (which there is for TCE). In a similar study, reduction of nitroaromatics was caused both by adsorbed iron on edge surfaces of clays as well as structural iron in the 2:1 smectite clays (Hofstetter et al 1999(Hofstetter et al , 2003.…”
Section: Description Of Tasksmentioning
confidence: 84%
“…The role of the 2:1 smectite clays may be significantly different for NDMA degradation, since there is no direct link between NDMA degradation and adsorbed ferrous iron (which there is for TCE). In a similar study, reduction of nitroaromatics was caused both by adsorbed iron on edge surfaces of clays as well as structural iron in the 2:1 smectite clays (Hofstetter et al 1999(Hofstetter et al , 2003 There may be a small amount of H 2 production at magnetite surfaces in the reduced sediment, which could catalyze NDMA degradation rate through reaction with H 2 . Our previous research has shown that limited quantities of H 2 can be produced in the natural subsurface abiotically by release from mafic minerals (Stevens and McKinley 2000).…”
mentioning
confidence: 87%
“…They are mobile in groundwater and adsorption onto aquifer material is not significant (Schwarzenbach et al 1993). The highest concentrations of RDX (84 pg/L) and HMX (12 pg/L) were measured in a groundwater sample collected from 1047 ft, whereas the highest concentration of TNT (19 pg/L) was measured at 867 ft. Degradation products of TNT that were detected include 4-A-2,6-DNT and 2-A-4,6-DNT, which are stable under anaerobic conditions (Hofstetter et al 1999). Other HE-related compounds analyzed for but not detected include 1,3-dinitrobenzene, tetryl, nitrobenzene, 2,6-dinitrotoluene, 2,4-dinitrotoluene, 2-nitrotoluene, 4-nitrotoluene, and 3Znitrotoluene.…”
Section: Groundwaterannual Status Report-fy99mentioning
confidence: 99%
“…67,68 The degradation process can also be affected by a number of environmental conditions, such as pH, and the presence of cations or organic material in the system. 69 Alternatively, RDX undergoes both photolysis and hydrolysis to form several byproducts. 70,71 Several of these byproducts (e.g., 4-nitro-2,4-diazabutanal) are soluble and do not hydrolyze; however, once RDX degrades into amide intermediates, the amides rapidly undergo hydrolysis.…”
Section: Fate and Transportmentioning
confidence: 99%